Penerapan Media Simulasi Wokwi dalam Meningkatkan Hasil Belajar Mahasiswa pada Mata Kuliah Sensor dan Transduser - Sukarman Purba; Erwinsius Simamora; Ano Jastin Sinaga; Rivan Permana Putra Simatupang; Zul Khaizar (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
Learning in the Sensor and Transducer course requires both conceptual understanding and practical experience. However, limitations in laboratory equipment, practice time, and operational costs often hinder the learning process. This study aimed to investigate the implementation of the Wokwi simulation platform in improving students’ learning outcomes in the Sensor and Transducer course. A quantitative approach with a one-group pretest–posttest design was employed involving students of the Electrical Engineering Education Study Program at Universitas Negeri Medan. Data were collected through learning achievement tests and student response questionnaires. The results showed a significant improvement in students’ average scores, increasing from 63.78 in the pretest to 94.72 in the posttest. Furthermore, questionnaire results indicated that students had highly positive perceptions of Wokwi as a learning medium due to its ease of use, interactive features, and ability to facilitate practical understanding of sensor concepts. Therefore, Wokwi is an effective technology-based learning medium for enhancing student learning outcomes in the Sensor and Transducer course.